Biochemistry & molecular biology of plants - Buchanan, Bob B.; Gruissem, Wilhelm; Jones, Russell L. (John Wiley & Sons Inc., 2015)
A major new edition of this highly successful, authoritative, superbly illustrated text * Distinguished, internationally renowned Editors * Completely revised with over half of the chapters having a major rewrite * Includes two new chapters on signal transduction and responses to pathogens